PERICRANIAL - ONLAY CRANIOPLASTY TECHNIQUE - Tomevska, Ana; Mikjunovikj, Mikjun; Jovanoski, Tomislav; Vesilevski, Aleksandar; Shibakoska, Ana; Mikjunovikj, Emilija; Dodevski, Ace (Journal of Morphological Sciences, 2024)
Cranioplasty is a neuroplastic surgical technique used to repair cranial defects in order to restore functional anatomy, preventing any neurological drawbacks and taking into account the cosmetic issues. This procedure is required for patients undergoing decompressive hemicraniectomy for life-threatening conditions such as diffuse traumatic brain injury, acute subdural hematoma, intracerebral hemorrhage, and severe ischemic stroke. It involves utilizing autologous or non-autologous bone flaps, with various preservation methods such as subcutaneous abdominal tissue or cryopreservation. Decompressive craniectomy, a procedure used to alleviate intracranial pressure, involves the excision of skull segments to accommodate cerebral edema. Cranioplasty is associated with high complication rates. The timing of the cranioplasty procedure, its potential benefits and risks, should be calculated in each individual case.     Case report:  A 59-year-old patient who underwent a decompressive hemicraniectomy because of diffuse traumatic brain injury and acute subdural hematoma, presents with mild right sided hemiparesis, speech disorder, episodes of neck dystonia, psycho-organic syndrome and sinking skin flap syndrome. Pericranial-onlay cranioplasty was preformed using autologous bone flap previously implanted in his abdominal pouch. The surgical procedure was uneventful with satisfactory cosmetic results and improved neurological function. Cranioplasty after decompressive hemicraniectomy is necessary for improving neurological function of the brain and improving the aesthetic appearance of the patient. Personalized approach is used for the skull reconstruction depending on the resources of the institution and the surgical technique used by the staff.     Keywords: cranioplasty, decompressive hemicraniectomy, autologous bone graft, abdominal pouch.